UJI DEFISIENSI FOSFOR PADA BEBERAPA KLON TEBU (Saccharum officinarum L) SECARA IN VITRO - Utama, Putra; ., Susiyanti; Fatmawaty, Andi Apriany (Jurnal Agroekoteknologi, 2009)
ABSTRACTPhosphorus deficiency test research in several clones of sugar cane produced in seven months has been carried out during 25 April-25 November 2007 in the Laboratory ICBB, Nagrak Cilubang-Bogor. The purpose of this research is to influence the interaction between phosphoru concentration of sugarcane clones. This research using completely randomized design arranged as a factorial with two factors. The first factor is composed of sugarcane clones with three levels different there are: cv. Triton (V1), cv. PSJT 94-41 (V2), and cv. PA 175 (V3). The second factor is the addition of KH2PO4 in the culture medium modification of P deficiency consisting of six levels, namely: 0 mg/l KH2PO4 (D1), 34 mg/l KH2PO4 (D2); 68 mg /l KH2PO4 (D3); 102 mg /l KH2PO4 (D4); 136 mg /l KH2PO4 (D5) and 170 mg /l KH2PO4 (D6). Results obtained by the interaction between concentration of P given by clones tested in vitro, and sugarcane cv PA 175 best growth on media by providing 170 mg /l KH2PO4Key words: Saccharum officinarum L, phosphorus, devisiensi, in vitro